Characteristic Features and Neuroendocrine Regulation of Estrous Cycle in Rodents: New Formulation for Calculation - Praveenkumar S. Kondaguli; Vani, V; Chaitra R. Sharma; Laxmi S. Inamdar (Doddamani) (Contemporary Research and Perspectives in Biological Science Vol. 8, 2025)
Aim: The present review aims to provide detailed information about the Phases, characteristic features, and neuroendocrine regulation of the estrous cycle in rodents. Background and Methodology: The estrous cycle is the sequential events of the reproductive cycle in mammals other than primates (menstrual cycle). The short length of the estrous cycle of female rodents makes them ideal for investigating changes occurring during the reproductive cycle. The estrous cycle in rodents lasts 4-5 days and has 4 phases, proestrus, estrus, metestrus, and diestrus. These phases of the estrous cycle are determined based on the proportion of three different types of cells i.e., leukocytes, nucleated epithelial cells, and cornified epithelial cells present in the vaginal secretions. Microscopic evaluation of these cells present in vaginal smears is the most accepted way of assessing of estrous cycle. The duration and relative proportion of these cell types vary among species. Besides, cyclic ovarian function is under the control of the hypothalamic-pituitary-ovarian (HPG) axis. The hypophyseal gonadotrophs responding to gonadotropin-releasing hormone (GnRH), synthesize and release luteinizing hormone (LH) and follicle-stimulating hormone (FSH), which induce ovarian folliculogenesis, ovulation and formation of corpus luteum (CL). Greatest GnRH release triggers the preovulatory surge of gonadotropins on the afternoon of proestrus, subsequently plasma estrogen level reaches a peak which stimulates a small surge in FSH followed by a marked surge of progesterone. Ovulation occurs during estrus where females are highly receptive to males. Further, mammals are classified based on ovulation patterns as coitus-induced ovulators and spontaneous ovulators. The rats and mice come under the category of spontaneous ovulators. Species whose estrous period is confined to a certain period of the year are referred to as seasonal breeders. Comparative Account and New Formulation: The present review attempts to provide a comparative account of phases of estrous cyclicity among laboratory mammals, viz. mice, rats and hamsters, and comparative aspects of estrous cyclicity in these mammals, and its neuroendocrine regulation. This report brings out various methodologies, comparisons, and details of formulations utilized in earlier studies to calculate the estrous cyclicity among multiple groups. Conclusion: This is the first review demonstrating a new formulation for evaluating the estrous cyclicity parameters, unveiling a precise and accurate formula to calculate the duration of different phases of the estrous cycle during the experimental period in mice. The details of this protocol can be utilized as a reproductive index for spontaneous ovulating mammals.